Gender differences in the supply of alcohol to adolescent daughters and sons. (4th July 2021) - Najman, Jackob M.; Clare, Philip J; Kypri, Kypros; Aiken, Alexandra; Wadolowski, Monika; Hutchinson, Delyse; Slade, Tim; Bruno, Raimondo; Vogl, Laura; Degenhardt, Louisa; Mattick, Richard. P.
ABSTRACT: Background : Parents are the main supplier of alcohol to children but it is not known whether mothers and fathers equally contribute to the supply of alcohol to their female and male children as these children transition to adulthood. Objectives : i) to determine whether the gender of the parent is associated with the gender of the adolescent offspring when alcohol is supplied and ii) whether the gender of the parent supplying is associated with gender differences in adolescent binge drinking and alcohol related harms. Methods : Longitudinal cohort of 1, 927 (males = 1052) Australian adolescents (mean age 12.9 years), recruited in 2010/11 from schools in Australia and surveyed annually for six years. We assessed the association between adolescent and parent gender related to subsequent adolescent drinking, binge drinking (>4 standard drinks), and alcohol-related harms. Results : At mean age of 12.9 years about one in ten children report parental supply of alcohol which increases to about four in ten children by 17.8 years. Mothers consistently more often supply their daughters with alcohol than their sons, [Wave 5 OR 1.77 (1.53, 2.05)], while mothers less often supply sons than their daughters, [Wave 5 OR 0.82 (0.71, 0.95)]. Mothers' supply of alcohol to daughters predicts substantially increased odds of daughters binge drinking, [OR 1.67 (1.10, 2.53)] and experiencing alcohol related harms, [OR 1.65 (1.10, 2.48)]. Conclusion : There is a need to involve both mothers and fathers and to equally target female and male children in programs to reduce the harmful consequences of parental supply of alcohol to their children.